Ultrahigh magnetic field spectroscopy reveals the band structure of the 3D topological insulator Bi$_2$Se$_3$ - Miyata, A; Yang, Z; Surrente, A; Drachenko, O; Maude, D; Portugall, O; Duffy, L; Hesjedal, T; Plochocka, P; Nicholas, R (2017)

(untitled)
We have investigated the band structure at the Γ point of the three-dimensional (3D) topological insulator Bi2Se3 using magneto-spectroscopy over a wide range of energies (0.55-2.2eV) and in ultrahigh magnetic fields up to 150T. At such high energies (E>0.6eV) the parabolic approximation for the massive Dirac fermions breaks down and the Landau level dispersion becomes nonlinear. At even higher energies around 0.99 and 1.6 eV, new additional strong absorptions are observed with a temperature and magnetic-field dependence which suggest that they originate from higher band gaps. Spin orbit splittings for the further lying conduction and valence bands are found to be 0.196 and 0.264 eV.